Fischer 344 Rat: A Preclinical Model for Epithelial Ovarian Cancer Folate-Targeted Therapy. Issue 7 (September 2015) - Azaïs, Henri; Queniat, Gurvan; Bonner, Caroline; Kerdraon, Olivier; Tardivel, Meryem; Jetpisbayeva, Gulim; Frochot, Céline; Betrouni, Nacim; Collinet, Pierre; Mordon, Serge
Abstract : Objective: Ovarian cancer prognosis remains dire after primary therapy. Recurrence rates are disappointingly high as 60% of women with advanced epithelial ovarian cancer considered in remission will develop recurrent disease within 5 years. Special attention to undetected peritoneal metastasis and residual tumorous cells during surgery is necessary as they are the main predictive factors of recurrences. Folate receptor α (FRα) shows promising prospects in targeting ovarian cancerous cells. Our aim was to determine if the Fischer model described by Rose et al could be used to evaluate folate-targeted therapies in preclinical studies. Methods: NuTu-19 epithelial ovarian cancer cell line was used to induce peritoneal carcinomatosis in female Fischer 344 rats. FRα expression by NuTu-19 cells was assessed in vitro by immunofluorescence using "Cytospin®" protocol. In vitro folate-targeted compound uptake by NuTu-19 cells was evaluated by incubation of FRα-positive ovarian cancer cell lines (NuTu-19/SKOV-3/OVCAR-3/IGROV-1) with or without (control) a folate-targeted photosensitizer. Intracellular incorporation was assessed by confocal microscopy. Determination of in vivo FRα tissue expression by several organs of the peritoneal cavity was studied by immunohistochemistry. Results: NuTu-19 cells express FRα which allows intracellular incorporation of folate-targeted compound by endocytosis. FRα is expressed in tumor tissue, ovary, and liver. Peritoneum, colon, small intestine, and kidney do not express the receptor. Conclusions: Female Fischer 344 rat is an inexpensive reproducible and efficient preclinical model to study ovarian peritoneal carcinomatosis folate-targeted therapies. Abstract : Supplemental digital content is available in the text.